Knowledge and uptake of e-learning among African students during the COVID-19 lockdown: Online education, impacts of COVID-19 (Journal of Applied Learning and Teaching, 2022)
This study evaluates the knowledge and uptake of e-learning among students of Ado-Odo Ota local government area, Nigeria during COVID-19 lockdown. The study was a descriptive cross-sectional survey of primary and secondary school students conducted from January to February, 2021. Data were analyzed with IBM-SPSS version 25.0. Knowledge of e-learning was (28.4%); 14.7% have ever participated in e-learning, and 8.4% participated during the lockdown. Only 26.6% had access to the internet, computers (1.1%), and phones/tablets (5.5%). The primary reason for not participating in e-learning was lack of awareness (78.2%); no money to buy data (8.9%), and no computers/android/tablets (12.9%). Overall, 57.1% attended tutorials outside their homes but almost 43.4% said three people shared a bench during the tutorials. Education does not have to be shut down due to a pandemics and students should not be limited to only classroom teaching methods but be introduced to e-learning. Teachers also need to be trained on conducting e-training..